Mechanism and Disease Association With a Ubiquitin Conjugating E2 Enzyme: UBE2L3 - Zhang, Xiaoxia; Huo, Chengdong; Liu, Yating; Su, Ruiliang; Zhao, Yang; Li, Yumin (Frontiers in Immunology, 2022)
Ubiquitin conjugating enzyme (E2s) is an important component of post-translational protein ubiquitination pathway, which mediates the transfer of activated ubiquitin to substrate protein. UBE2L3, a member of the ubiquitin conjugating enzyme (E2s) protein family, is involved in the ubiquitination of dozens of proteins and regulates nuclear factor kappa- B (NF-κB), GSK3β/p65 and several other important signaling pathways. It is reported that UBE2L3 might be abnormally expressed in immune diseases and tumor and Parkinson's disease, and is involved in the initiation and progression of these diseases. In this review, we mainly focus on the structure, activity, signaling pathway and related diseases of UBE2L3 and discuss the related challenges.